2001
DOI: 10.1054/bjoc.2001.1882
|View full text |Cite
|
Sign up to set email alerts
|

The expression of vascular endothelial growth factor C and its receptors in non-small cell lung cancer

Abstract: Expression of vascular endothelial growth factor (VEGF)-C and that of its receptors were assessed in non-small cell lung cancer. Immunohistochemistry revealed positive VEGF-C expression in 38.7% (24/62) of the patients studied. A significant positive correlation was found between VEGF-C in cancer cells and VEGF receptor-3 (VEGFR-3) in vascular endothelial cells, but not between VEGF-C in cancer cells and VEGFR-2 in endothelial cells. In this cohort of lung cancer patients, VEGF-C expression was significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
122
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 23 publications
(25 reference statements)
11
122
1
2
Order By: Relevance
“…The present study also demonstrated that the survival of patients with stage I NSCLCs was significantly lower in patients with hypervascular tumours than in patients with hypovascular tumours. In addition, VEGF-C expression, another member of the VEGF family and reported to induce lymphangiogenesis (Skobe et al, 2001), was also associated with the prognosis of stage I patients, as reported previously (Kajita et al, 2001;Arinaga et al, 2003). Furthermore, previous clinical studies have shown that reduced expressions of several metastatic suppressor genes, including E-cadherin (Sulzer et al, 1998;Liu et al, 2001), MRP-1/CD9, and KAI1/CD82 , are also associated with nodal metastases and a poor prognosis of patients with stage I NSCLCs.…”
Section: Discussionsupporting
confidence: 73%
“…The present study also demonstrated that the survival of patients with stage I NSCLCs was significantly lower in patients with hypervascular tumours than in patients with hypovascular tumours. In addition, VEGF-C expression, another member of the VEGF family and reported to induce lymphangiogenesis (Skobe et al, 2001), was also associated with the prognosis of stage I patients, as reported previously (Kajita et al, 2001;Arinaga et al, 2003). Furthermore, previous clinical studies have shown that reduced expressions of several metastatic suppressor genes, including E-cadherin (Sulzer et al, 1998;Liu et al, 2001), MRP-1/CD9, and KAI1/CD82 , are also associated with nodal metastases and a poor prognosis of patients with stage I NSCLCs.…”
Section: Discussionsupporting
confidence: 73%
“…[4][5][6] Expression of VEGFR-3 is highly restricted to lymphatic endothelial cells and stimulated by only VEGF-C and -D. [7][8][9] VEGF-C overexpression in breast cancer potently increases intratumoral lymphangiogenesis, resulting in enhanced metastasis to regional lymph nodes. 10 Several reports have described a significant correlation between VEGF-C expression, tumor lymphangiogenesis and regional lymph-node metastasis in some tumors. [11][12][13][14][15][16][17][18] Therefore, inhibition of VEGF-C activity or disabling VEGF-C receptor function may be useful to inhibit tumor growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, an association of VEGF-C with nodal metastasis is still unclear in patients with nonsmall cell lung carcinoma (NSCLC). [17][18][19][20][21][22] Niki and coworkers 23 described low VEGF-D mRNA levels in tumor tissue samples of lung adenocarcinoma patients with lymph node metastasis, although these samples showed high mRNA levels of VEGF, VEGF-B, and VEGF-C. VEGFR-3 expression was observed in blood and lymphatic vessels in stroma of various malignancies 24 -26 including NSCLCs. 17,18,20,27,28 However, there has been no report to assess the clinicopathologic significance of VEGF-C and VEGFR-3 in patients with TNM classification T1 lung adenocarcinoma (tumor size of Յ 3 cm less in diameter).…”
Section: Introductionmentioning
confidence: 99%